Entropy as a factor of influence on energy security management of enterprises - Prokhorova, Viktoriia; Budanov, Mykola (Technology audit and production reserves, 2024)
Energy security management of the enterprise in conditions of entropy is an important aspect that includes adaptation to changes in the external environment and internal processes. The object of research is entropy, as a measure of uncertainty and chaos in energy systems, which affects the energy security management of enterprises. The problem of a comprehensive approach to the study and implementation of methods for calculating entropy indicators, which would take into account entropy in the energy security management, is solved. The conducted analysis shows how the level of entropy in the supply of energy resources, in particular coal, electricity and alternative sources, affects the stability, sustainability and adaptability of management strategies aimed at ensuring energy security management. The essence of the obtained results is that the study shows the importance of energy security management of enterprises in the conditions of entropy, which is a measure of uncertainty in energy systems. Entropy acts as a key factor influencing the energy security management, as it reflects the level of chaos and uncertainty in the supply of energy resources. It is shown that the level of entropy directly affects the stability and adaptability of management strategies, which allows enterprises to better respond to external challenges and internal risks. The use of mathematical models, in particular Shannon's formulas, makes it possible to quantitatively assess the level of entropy and identify potential risks arising in energy systems. Awareness of the impact of entropy on management decisions helps enterprises to optimize processes, predict threats and reduce negative consequences. The research results reflect the complex interplay between entropy, management strategies and external challenges, emphasizing the importance of an adaptive approach in energy security management. The research focuses on practical aspects. From a practical point of view, awareness of the impact of entropy on management decisions allows enterprises to optimize management processes, predict potential threats, and reduce the negative consequences of external and internal risks. The results of this research can become the basis for the formation of new management strategies capable of effectively responding to the modern challenges of the energy sector.